Screening for celiac disease in the general population and in high-risk groups - Ludvigsson, Jonas F.; Card, Timothy R.; Kaukinen, Katri; Bai, Julio; Zingone, Fabiana; Sanders, David S.; Murray, Joseph A. (SAGE, 2014)
BACKGROUND: Celiac disease (CD) occurs in approximately 1% of the Western population. It is a lifelong disorder that is associated with impaired quality of life (QOL) and an excessive risk of comorbidity and death.